The Role of Social Capital in Improving Quality Village- Owned Enterprises (BUMDES) - Fatimah Tolu Ronauli Gurning; Julia Ivanna (RIRAI Publisher, 2022)
This study aims to determine the role of social capital in improve the quality of BUMDes through the management of the Aek Parulian bathing tourism object in Sipan Village, Sarudik District, Central Tapanuli Regency. The research method used is descriptive qualitative, the use of this research method is to describe the data results from research in the field. The subjects in the study were the Sipan Village Head, BUMDes Management and Managers, and the Sipan Village community. Types of data in this study primary data and secondary data. Data collection techniques used are observation, interviews, and documentation. Data analysis techniques used in this study are data reduction, data presentation, and drawing conclusions. Based on the results of the study, it shows that social capital has a role in the establishment of Gabe BUMDes and the management of Unit Business of Aek Parulian bath in Sipan Village. The elements of social networks and trust have a bigger role, namely the existence of social relations, communication and interactions that have a good effect on the level of participation and community involvement in deliberation activities held as a forum for all parties to exchange ideas. As well as the values ​​that are applied from the aspect of competence and honesty by the board and manager of the Gabe BUMDes which increase the trust of the village community. Meanwhile, the norm element has a smaller role which is manifested in the form of written regulations (village regulations) and to enforce discipline, behavior control and guidelines for the management of BUMDes Gabe and Unit Business of Aek Parulian Bath.